Solar Flare Effects on 150‐km Echoes Observed Over Jicamarca: WACCM‐X Simulations. Issue 20 (28th October 2019) - Pedatella, N. M.; Chau, J. L.; Vierinen, J.; Qian, L.; Reyes, P.; Kudeki, E.; Lehmacher, G.; Oppenheim, M.
Abstract: Jicamarca Radio Observatory observations and Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension (WACCM‐X) simulations are used to investigate the effects of the 7 September 2005 X‐17 solar flare on 150‐km echoes, electron densities, and vertical plasma drifts. The solar flare produces a remarkably similar response in the observed 150‐km echoes and simulated electron densities. The results provide additional evidence of the relationship between the background electron density and the layering structure that is seen in 150‐km echoes. The simulations also capture a similar rapid decrease in vertical plasma drift velocity that is seen in the observations. The simulated change in vertical plasma drift is, however, weaker than the observed decrease at the longitude of Jicamarca, though it is stronger east of Jicamarca. The effect of the solar flare on the vertical plasma drifts is primarily attributed to changes in conductivity due to the enhanced ionization during the solar flare. Key Points: There is a good agreement between observed morphology of 150‐km echoes and simulated electron densities during a solar flare The results support the hypothesis that layering of 150‐km echoes is connected to electron densities Decrease in vertical plasma drift during the solar flare can be attributed to changes in E region conductivity